JWST/MIRI Detection of [Ne v], [Ne vi], and [O iv] Wind Emission in the O9 V Star 10 Lacertae - David R. Law; Calum Hawcroft; Linda J. Smith; Alexander W. Fullerton; Christopher J. Evans; Karl D. Gordon; Nimisha Kumari; Claus Leitherer (The Astrophysical Journal Letters)
We report the detection of broad, flat-topped emission in the fine-structure lines of [Ne v ], [Ne vi ], and [O iv ] in mid-infrared spectra of the O9 V star 10 Lacertae obtained with James Webb Space Telescope/Mid-Infrared Instrument. Optically thin emission in these high ions traces a hot, low-density component of the wind. The observed line fluxes imply a mass-loss rate of >3 × 10 ^−8 M _⊙ yr ^−1 , which is 1 order of magnitude larger than previous estimates based on UV and optical diagnostics. The presence of this hot component reconciles measured values of the mass-loss rate with theoretical predictions and appears to solve the “weak wind” problem for the particular case of 10 Lac.